(untitled) (Indian Journal of Arid Horticulture, 2020)
The soils of arid region are very poor in macro and micronutrients as well as physical properties of soil. The proper soil depth, hard layer/pan are also a problem in some parts for better orchard establishment. The soils of the north- western arid region is known as ’desert soils’ and ’grey brown soils’ comes in the order of Aridisols which is light textured. The soils often have high salinity. The ground water resource is not only inadequate due to poor surface and sub-surface drainage but is also saline in nature. The irrigation water resources in the region are seasonal rivers and rivulets, surface wells and some runoff water storage devices (e.g. nadi, tanka, khadins) and canal irrigation in arid region. Thus, the water resources in arid region are inadequate and can irrigate only just 4% of the area. The annual average rainfall in arid region is very low, varies from 100 mm in north-western sector of Jaisalmer to 450 mm in the eastern boundary or arid zone of Rajasthan. Most of the rainfall occurs during July-September in about 19-21 rain spells. Due to low and unpredictable rainfall pattern in arid region, suitable technology is required to increase productivity. Water is precious input in hot arid region of the country therefore, adoption of micro-irrigation system is advantageous to save water and enhance productivity. For arid environment, the variety is needed which are resistant to biotic and abiotic stresses for sustainable production.